2014
DOI: 10.1098/rsbl.2014.0291
|View full text |Cite
|
Sign up to set email alerts
|

Field evidence for earlier leaf-out dates in alpine grassland on the eastern Tibetan Plateau from 1990 to 2006

Abstract: Worldwide, many plant species are experiencing an earlier onset of spring phenophases due to climate warming. Rapid recent temperature increases on the Tibetan Plateau (TP) have triggered changes in the spring phenology of the local vegetation. However, remote sensing studies of the land surface phenology have reached conflicting interpretations about green-up patterns observed on the TP since the mid-1990s. We investigated this issue using field phenological observations from 1990 to 2006, for 11 dominant pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…This approach is relatively flexible [52,53] with fewer data requirements than other PET estimation approaches, which provides advantages in the Tibetan Plateau which has very limited in situ surface meteorology observations. As the growing season of the TP grasslands generally starts around May [5,25,35,54], we used the period from March to May to represent pre-season climate conditions for spring onset. The use of partial correlation analysis allows for distinguishing phenological effects from individual environmental variables while accounting for the interactive effects of other contributing variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is relatively flexible [52,53] with fewer data requirements than other PET estimation approaches, which provides advantages in the Tibetan Plateau which has very limited in situ surface meteorology observations. As the growing season of the TP grasslands generally starts around May [5,25,35,54], we used the period from March to May to represent pre-season climate conditions for spring onset. The use of partial correlation analysis allows for distinguishing phenological effects from individual environmental variables while accounting for the interactive effects of other contributing variables.…”
Section: Discussionmentioning
confidence: 99%
“…Over 80% of the study area (4592˘510 m) ranges between 4300 and 5000 m in elevation, and ecosystems within this elevation zone likely experience an earlier green-up of 6-8 days in response to a 1˝C rise in May air temperatures [16]. In-situ observations have documented different spring leaf-out dates between the TP meadow and steppe grasslands [35], so we divided the study domain into three sub-areas based on regional eco-geographic attributes [30]. Among the three eco-zones examined, Zone-3 is the warmest with a mean annual air temperature (T a ) of´1.07˝C, followed by Zone-2 (´3.83˝C) and Zone-1 (´4.67˝C).…”
Section: Study Areamentioning
confidence: 99%
“…The observed remote sensing patterns are interesting, yet they are unable to tease apart the mechanisms driving the observed changes in phenology because they are not experimental and they cannot detect flowering (Shen et al., ; Wang, Meng, et al., ). Moreover, some experimental and observational studies have revealed that warming accelerated the phenology on the Tibetan Plateau (Chen et al., ; Meng et al., ; Wang, Meng, et al., ; Wang, Wang, et al., ; Zhou et al., ). Given asymmetric warming on plant phenology has been unexplored, it remains unclear how differences in winter and spring temperatures control spring phenology.…”
Section: Introductionmentioning
confidence: 99%
“…Statistically significant temporal trends in long-term phenological time series are not always detected using a linear regression model because phenological changes may not exhibit a monotonic trend (Menzel et al 2006, Shen et al 2014, Zhou et al 2014. However, unlike linear regression SSA does not impose linearity on the time series and has been successfully used to describe the complex variation in spring phenology of Figure 9.…”
Section: Discussionmentioning
confidence: 99%